Analisa Kecelakaan Lalu Lintas di Ruas Jalan Bypass Ngurah Rai Kota Denpasar - Nengah Riana; Yanuarius Reinaldi Nenta; I Gusti Ngurah Nyoman Wismantara (Jurnal Ilmiah Telsinas, 2022)
The Ngurah Rai Bypass Road in Denpasar City is one of the roads that has a high accident rate. The Ngurah Rai Bypass accommodates traffic flow from the direction of Nusa Dua towards Denpasar City where the number of vehicles continues to increase every year, causing road conditions to become more congested and accidents to occur. The purpose of this study is to analyze the characteristics of traffic accidents on the Ngurah Rai Bypass Road and determine blacksites and blackspots. This study used a data collection method, namely secondary data for three years (2018 – 2020) obtained from the Denpasar City Police Traffic Unit. For calculations using the EAN method or equivalent accident number which is one of several calculation methods to determine accident-prone areas and points. The results of the analysis show that the number of accident incidents over the past three years (2018-2020) totaled 277 incidents with accident characteristics, namely the victim class with the highest level of severity was minor injuries (LR) of 298 people with a percentage of 67%, the highest accident time occurred at light time (06.00 -18.59) as many as 174 incidents with a percentage of 62.8%, the highest type of vehicle involved in an accident, namely motorbikes, 182 incidents with a percentage of 60.5%, the highest gender involved in an accident, namely men 261 people with a percentage of 58.7%, The highest age of victims involved in accidents was 17-30 years with 268 people with a percentage of 60.2%, the highest cause of accidents were road users (riders and pedestrians) with 260 incidents with a percentage of 93.9%. The 7 road segments that are categorized as blacksites on the Bypass Ngurah Rai road in Denpasar City are segment 25 (km 24-25), segment 28 (km 27-28), segment 13 (km 12-13), segment 9 (km 8- 9), segment 18 (km 17 – 18), segment 14 (km 13 – 14), segment 15 (km 14 – 15). Seven points are categorized as blackspots on the Denpasar City Bypass Ngurah Rai road, namely segment 25 (km 24.6 – 24.9), segment 28 (km 27.4 – 27.8), segment 13 (km 12 – 12.7), segment 9 (km 8.7 – 8.9), segment 18 (km 17 – 17.8), segment 14 (km 13 – 13.6), segment 15 (km 14.3 – 15).